Subsequent vaginal delivery in a case reverted by Dobbins operation for acute uterine inversion: A case report - Rana, Ashma; Gurung, Geeta; Pariyar, Jitendra; Pokharel, Sunil; Adhikari, Shilu (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A woman with a history of laparotomy and corrective abdominal surgery for acute puerperal uterine inversion reverted by division of the inversion ring anteriorly "Dobbins's operation" subsequently was successful to undergo assisted vaginal breech delivery arriving at second stage of labor warranting, manual removal of placenta which was complied with the management of PPH. This case is reported because of the rarity of uterine inversion itself in the first place. Next because of the conception taking place spontaneously after morbid puerperal period and then the pregnancy advancing to term: all the management beginning from correction of uterine inversion to retained placenta being handled in the same facility a rare event too in our set up. Key words: Uterine inversion and subsequent birth, manual removal of the placenta. doi:10.3126/njog.v2i2.1462 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 78 - 80